Examining the context, connection and complexity of collaborative doctoral programs in international business - Boncheva, Katerina; Gajewska-De Mattos, Hanna; Griffith, David A.; Pirrone, Giuseppe; Šilenskytė, Aušrinė; Tonn, Alexander (Emerald, 2026)
Purpose By using the 3Cs framework (i.e. context, connection and complexity), this paper aims to examine the state of doctoral education in the field of international business (IB) and the collaborative IB doctoral programs, defined as programs formed through collaborations between multiple universities and/or associations. Design/methodology/approach We examine multiple collaborative programs in doctoral education in IB (i.e. the AIB-CIBER Doctoral Academy, Nordic Research School of IB, Emerging Scholars from Emerging Markets Program and the Finnish Graduate School of International Business) under the 3Cs framework. This examination allows for a better understanding of how these programs prepare students to nurture the IB disciplinary and societal demands. Findings We suggest that enhancing doctoral education in IB to meet the challenges of understanding context, connection and complexity, requires extending both formal and informal components of doctoral programs, beyond home institutions of doctoral researchers, with an increased emphasis on informal aspects of doctoral training and an increased focus on students as learners striving for excellence. These components, which are a particular strength of collaborative IB doctoral programs, can positively shape scholarship and practices in the field of IB. Originality/value This paper provides a contemporary examination of doctoral education in the field of IB beyond the predominant focus on within-institution doctoral training elements and enhancements that could positively influence the context, connection and complexity of IB doctoral education globally.
Keywords: Doctoral education; 3Cs framework; Formal and informal doctoral training; International business; Collaborations; fi=Strateginen johtaminen|en=Strategic Management|